Better Screening Value of Sylvian Fissure Ratio on Cognitive Decline Among Female Compared to Male: An Observational Study in Elderly Patients With Cerebral Small Vessel Disease in Soochow - Qin, Yiren; Ai, Dannan; Jordan, Ashly E.; Guo, Xiaoning; Li, Tan; Diao, Shanshan; Zhao, Hongru; Liu, Yang; Xue, Qun; Wang, Yueju; Fang, Qi (Frontiers in Neuroscience, 2021)
Background Cognitive decline (CD) occurs frequently in elderly patients with cerebral small vessel disease (CSVD). In China, elderly patients are more likely to enter healthcare in community hospitals where no Magnetic Resonance Imaging (MRI) is available. This study aimed to explore the screening value of sylvian fissure ratio (SFR) on CD, and compare its gender difference from community-transferred patients. Methods We performed a single-center, observational study (collected between April 1, 2016 and March 1, 2019) to evaluate the association between Montreal Cognitive Assessment (MoCA) and SFR in 203 eligible community-transferred patients. Baseline characteristics of patients were collected during hospitalization. Multiple linear regression analyses were used to estimate the effect of variables on MoCA, and interactions between select variables were analyzed in different models. Receiver operating characteristic (ROC) curve analysis was used to evaluate the discriminative effect of SFR to severe CD. Results We identified that a meaningful SFR cutoff of 0.05 had important screening value (likelihood ratio test, P=0.067) on CD. The ratio had a lower screen value in males when compared to females (Adjusted β, -5.54; 95% CI, -8.78 to -2.30 vs Adjusted β, -1.01; 95% CI, -2.84 to 0.82). The gender difference was further verified by ROC curve analysis, in which this discriminative effect was more potent in females (from 0.878 to 0.948) compared to males (from 0.838 to 0.837 ). Conclusions A SFR of 0.05 may be more useful to distinguish CD in female patients with CSVD than male patients in whom the syndrome is suspected clinically.